Cervical Cancer and its Probable Ayurvedic Approach - Sharma, Shalvi; Dash, Bhagya Ranjan; Bharathi, K; Choudhary, Poonam (International Research Journal of Ayurveda & Yoga, 2021)
Cervical Cancer is the second most common cancer among women worldwide. Over 500,000 women worldwide die of cervical cancer annually. Human Papilloma Virus (HPV – mainly high risk type) is the main cause of cervical carcinogenesis. Worldwide, the prevalence of HPV in cervical tumors is 99.7%1. Approximately every 47 minutes a woman is diagnosed with cervical cancer. Among the 500,000 new cases each year, nearly 75% occur in developing countries1. Cervical cytological testing has reduced the incidence of cervical cancer by 70%1. As most of the cervical cancers are preventable so it become very important to diagnose them at an early treatable stage using appropriate diagnostic tools and finding new Ayurvedic measures to prevent and cure the disease so as to decrease the morbidity and mortality.